IMPLEMENTASI KURIKULUM 2013 DALAM MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK USIA DINI DI TK KASIH IBU KOTA JAMBI - Azzahra Sumaya; Eka Ribby Oktavia Rahmadani; Jessica Sharon siagian; Melati Susianti Marbun; Siti Mupadillah; Winda Sherly Utami; Sri Indriani Harianja (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to examine the implementation of the 2013 curriculum in developing the cognitive abilities of early childhood at the Kasih Kindergarten, Ibu Jambi. This research uses descriptive research with an exploratory approach. The use of this method is intended to be able to describe situations that occur directly. Data collection techniques in this research used observation and interview. The research subjects were early childhood children at the Kasih Kindergarten in Jambi City. The results of the research included that 20 children in the class had optimal cognitive abilities. It is proven by the results of observations that children are able to carry out activities such as saying numbers, saying the names of body parts and are also able to think creatively and this is in accordance with the 2013 curriculum.